A Hypothetical Vascular Stent with Locally Enlarged Segment and the Hemodynamic Evaluation. (25th February 2020) - Niu, Yudi; Sun, Anqiang; Wang, Zixuan; Yao, Chenghong; Song, Juxingsi
Abstract : Among the interventional stenting methods for treating coronary bifurcation lesions, the conventional treatments still have disadvantages, which include increased intervention difficulties or inadequate supply of blood flow to side branches and may alter the physiological function of downstream organs. Thus, the optimized design of stent geometry needs to be improved based on the specific shape of branches to minimize the complications of inadequate blood flow to the downstream organs and tissues. Our research used 3D modeling and fluid dynamics simulation to design and evaluate a new stent with locally enlarged segment by altering the proportion and length of enlarged surface area based on Bernoulli's equation. The aim is to increase the pressure and blood flow supply at side branches. According to series of blood flow simulations, the stent with 10% enlargement of surface area and length of 3 folders of stent diameter was assigned as the optimized design. The results revealed that by using this design, according to the simulation results, the average pressure on side branches increased at the rate of 43.6%, which would contribute to the adequate blood supply to the downstream organs. Besides, the average wall shear stress (WSS) at sidewalls increased at 9.2% while the average WSS on the host artery wall decreased at 14.1%. There is in the absent of noticeable rise in the total area of low WSS that blows the threshold of 0.5 Pa. Therefore, the present study provides a new method to optimize the hemodynamics features of stent for bifurcation arteries.